Journalistic Representation in the Film Vina: Sebelum 7 Hari Regarding the Issue of Bullying in Indonesia: A Social Critique - Ritonga, Rohani; Saragih, Yoserizal (Program Pascasarjana UIN Sumatera Utara, 2025)
The film Vina: Sebelum 7 Hari portrays the true story of a teenage girl from Cirebon who became a victim of bullying that ultimately led to her death. This film serves not only as a medium of entertainment but also as a tool for social advocacy, raising public awareness about the dangers of bullying. Through a journalistic approach, the film presents a powerful visual representation of the psychological and social impacts of bullying, as well as the role of the media in shaping public perception.This study employs a semiotic analysis method based on John Fiske's perspective to examine how the film represents sexual violence against women and its effects on public perception. The findings reveal that the film features two scenes of sexual violence, which, when analyzed through semiotic theory, depict the realities of sexual violence, critique societal norms, illustrate patriarchal dominance, and highlight social apathy—all reflected through reflective, intentional, and constructionist representations.Moreover, the film also emphasizes the phenomenon of